2019
DOI: 10.9734/ajaees/2019/v30i130100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Farm Mechanization on Income of Farmers in Assam, India

Abstract: The study was conducted in Central Brahmaputra Valley and Upper Brahmaputra Valley Zone of Assam in India. The present study is an attempt to study the effect of mechanization on income and limiting factors of farm mechanization of the sample farms. Primary data of 240 sample farms by personal interview schedule method was used for examining the effect of farm mechanization on income along with limiting factors for mechanization adoption  . All data collected from sample farms pertains to the year 2014-15. Tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This, in turn, has a significant impact on farmers’ income. Firstly, improved mechanization enhances agricultural production efficiency, standardizes production processes, and leads to higher yields and better quality agricultural products 38 . This directly contributes to increasing agricultural income.…”
Section: Methodsmentioning
confidence: 99%
“…This, in turn, has a significant impact on farmers’ income. Firstly, improved mechanization enhances agricultural production efficiency, standardizes production processes, and leads to higher yields and better quality agricultural products 38 . This directly contributes to increasing agricultural income.…”
Section: Methodsmentioning
confidence: 99%
“…All the inquiries such as increase in production, increase in income, reduction in cultivation costs, loan accessibility, increase in purchasing power, and increased investment have set down to be significant at 1% level of significance clearly exhibited the effect of farm machineries in the paddy cultivation and economical benefit to the farmers. Hence it was observed that there was positive impact of farm mechanization on income [10,11,12]. Increased yield, reduced cost of cultivation merits of mechanization [13,14,15].…”
Section: Social Impactmentioning
confidence: 99%
“…Agricultural mechanization which entails the use of machines to perform several activities on the farm in order to save time, money spent on hiring of labour and most importantly increases the level of production which will automatically lead to a simultaneous increase in the farmer's income. The agricultural mechanization is an important support of modernity and development [3,4,5,6]. The choice of machinery and equipment to be used depends on several factors including the size of the farm, the relationship of complementarity or substitutability of the labour force and its price, the expected increase in production and the availability in markets of machinery and equipment for rental [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%